Construction of exogenous methanol, formate, and betaine modules for methyl donor supply in methionine biosynthesis - Shen, Zhen-Yang; Wang, Yi-Feng; Wang, Li-Juan; Zhang, Bo; Liu, Zhi-Qiang; Zheng, Yu-Guo (Frontiers in Bioengineering and Biotechnology, 2023)
Methionine is an essential sulfur-containing amino acid that finds widespread applications in agriculture, medicine, and food industries. However, the complex and multibranched biosynthetic pathway of methionine has posed significant challenges to its efficient fermentation production. In this study, we employed a modularized synthetic biology strategy to improve the weakest branched pathway of methionine biosynthesis. Three exogenous modules were constructed and assembled to provide methyl donors, which are the primary limiting factors in methionine biosynthesis. The first module utilized added methanol, which was converted into 5,10-methylene-tetrahydrofolate for methionine production, but was hindered by the toxicity of methanol. To circumvent this issue, a non-toxic formate module was constructed, resulting in a visible improvement of methionine titer. Finally, an exogenous betaine module was constructed, which could directly deliver methyl to methionine. The final strain produced 2.87 g/L of methionine in a flask, representing a 20% increase over the starting strain. This study presents a novel strategy for improving and balancing other metabolites that are synthesized through complex multibranched pathways.